Orthopedics between Milan and Mexico: a case from the late 19th century - Biehler-Gomez, Lucie; Porro, Alessandro (Medicina Historica, 2023)
A folder titled “Rovatti” was found among the documentation of the private collection of Enrico Rosmini in Milan. This folder contained correspondence related to the Pio Istituto dei Rachitici in Milan, a school dedicated to the care of children with skeletal deformities. These documents provide insight into the care of the patients of the Institute through a personal lens, that of the experience of a father struggling with his efforts to achieve financial security. The documents presented in this short paper constitute additional information to better reconstruct the history of Milanese medicine in a crucial period of transition towards modernity, the so-called belle époque.